Shakespeare studies. - Barroll, J. Leeds (John Leeds) 1928-.; University of Cincinnati; Vanderbilt University. Center for Shakespeare Studies (Cincinnati, Ohio University of Cincinnati, 1965)
Annual.
"An annual gathering of research, criticism, and reviews."
Editor: 1965-88, J.L. Barroll.
Inaugurated under the sponsorship of the University of Cincinnati."
Indexed in its entirety by: Humanities index 0095-5981.
Indexed selectively by: Index to book reviews in the humanities 0073-5892 1984-.
Indexed selectively by: MLA international bibliography of books and articles on the modern languages and literatures (Complete edition) 0024-8215.
Keywords: Shakespeare, William -- 1564-1616.